Tailoring Electronic Structure and Size of Ultrastable Metalated Metal–Organic Frameworks with Enhanced Electroconductivity for High‐Performance Supercapacitors. Issue 18 (18th March 2021) - Xia, Zhengqiang; Jia, Xu; Ge, Xi; Ren, Chongting; Yang, Qi; Hu, Jun; Chen, Zhong; Han, Jing; Xie, Gang; Chen, Sanping; Gao, Shengli
Abstract: Utilization of metal–organic frameworks (MOFs) as electrodes for energy storage/conversion is challenging because of the low chemical stability and poor electrical conductivity of MOFs in electrolytes. A nanoscale MOF, Co0.24 Ni0.76 ‐bpa‐200, possessing ultrahigh stability with uncommon semiconductor behavior ( σ =4.2×10 −3  S m −1 ) was fabricated. The MOF comprises a robust hydrophobic paddlewheel and an optimized Co/Ni ratio, with consequent control over MOF size and the degree of conjugation of the coligand. A DFT study revealed that appropriate Ni 2+ doping reduces the activation energy of the system, thus providing a higher carrier concentration, and the strongly delocalized N‐donor ligand notably increases the metal–ligand orbital overlap to achieve efficient charge migration, leading to continuous through‐bond (‐CoNi‐N‐CoNi‐)∞ conduction paths. These structural features endow the MOF with a good cycling stability of 86.5 % (10 000 cycles) and a high specific capacitance of 1927.14 F g −1 among pristine MOF‐based electrodes. Abstract : An elaborately designed 3D metal–organic framework (MOF) integrating excellent chemical stability and good conductivity was obtained through a combination of ligand delocalization, activation energy, and morphology parameters. The superiority of the as‐prepared pristine MOF‐based supercapacitor electrode was structurally and electrochemically identified in detail.